2017
DOI: 10.1002/prp2.316
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and anti‐inflammatory properties of novel, selective, and potent EP4 receptor antagonists

Abstract: Prostaglandin (PG) E2 is the key driver of inflammation associated with arthritic conditions. Inhibitors of PGE 2 production (NSAIDs and Coxibs) are used to treat these conditions, but carry significant side effect risks due to the inhibition of all prostanoids that play important physiological function. The activities of PGE 2 are transduced through various receptor sub‐types. Prostaglandin E2 type 4 receptor (EP4) is associated with the development of inflammation and autoimmunity. We therefore are intereste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…PGE 2 and its downstream effectors are potential targets for modulation of inflammation associated with OA (31,34). This randomized, double-blind, placebo-and active-controlled, multicenter clinical study investigated the efficacy of an mPGES1 inhibitor (LYA) and an EP4 antagonist (LYB) for the treatment of chronic OA pain and was designed to inform drug development for both human and animal health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGE 2 and its downstream effectors are potential targets for modulation of inflammation associated with OA (31,34). This randomized, double-blind, placebo-and active-controlled, multicenter clinical study investigated the efficacy of an mPGES1 inhibitor (LYA) and an EP4 antagonist (LYB) for the treatment of chronic OA pain and was designed to inform drug development for both human and animal health.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 exerts its biological effects by binding to four specific membrane-bound G protein-coupled receptors [EP1 (E-type prostanoid 1) to EP4]. Of the four receptors, EP4 is associated with the development of inflammation and autoimmunity and is not known to be associated with the direct modulation of other prostanoids (31). In 2016, a PGE 2 EP4 receptor antagonist (grapiprant) was approved for use in dogs, representing the first demonstration of efficacy for this new class of piprant drugs (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, experimental data in cellular and animal models have outlined a far more interesting pharmacological profile for selective EP4 receptor antagonists [ 11 , 41 ]. Whether they may offer an advantage as simple analgesics over existing drugs such as COX inhibitors is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To the contrary, another study showed that PGE2 inhibited IL-1b-induced expression of MMP1 and MMP13 via EP4 by suppressing MKK4-JNK MAPK-c-JUN pathway in human chondrocytes (127). Furthermore, the EP4 receptor mediates the PGE2-elicited inflammation and sensitization of sensory neurons, while EP4 inhibition contributes to the development of targeted therapies for antiinflammatory and analgesic effect in OA (128)(129)(130)(131). Grapiprant, an EP4 antagonist, has been approved for by the FDA treating OA pain in dogs (132,133).…”
Section: Prostaglandin Receptorsmentioning
confidence: 99%